Ways to improve the efficiency of Foundries of The Republic of Belarus - P. A. Vityaz; A. V. Tolstoy; M. A. Sadоkha (Литьë и металлургия, 2020)
The ways to improve the efficiency of foundries of the Republic of Belarus are presented. The list of the basic enterprises which activity is focused on increase of knowledge intensity of a gross product, reception of a final product with high added value is resulted. Plans of loading of production capacities of the basic organizations for the period till 2030, investment projects and actions for new construction and modernization of their foundries are considered. The main provisions of the development program of foundries of the Republic of Belarus for 2017-2030, its goals and objectives are presented.